Colonic invasive adenocarcinoma with squamoid morules: A case report - Akira Ishikawa; Hidenori Tanaka; Ken Yamashita; Koji Arihiro; Shiro Oka; Manabu Shimomura; Hideki Ohdan (DEN Open)
Abstract Colorectal adenomas with squamoid morules are rare; however, colorectal adenocarcinomas are even rarer. Herein, we present a case of colorectal adenocarcinoma with squamoid morules arising from the transverse colon. A 60‐year‐old Japanese man underwent a colonoscopy, and a Type 0‐Is polyp was detected in the transverse colon. The endoscopic findings suggested a high possibility of carcinoma invasion into the deep submucosa. However, endoscopic mucosal resection was performed due to the patient's preference. Histopathologically, the tumor cells mostly formed atypical glandular structures corresponding to adenocarcinomas. Solid nests were observed in parts of the tumor, composed of round, small to short spindles. Immunohistochemically, p63 was positive in some areas, CK20 was negative, and the Ki‐67 positive cell rate was almost zero, suggesting a squamoid morule. Based on the above findings, colorectal adenocarcinoma with a squamoid morule was diagnosed; only the fifth case was reported worldwide. Squamoid morules should be carefully differentiated from squamous components of adenosquamous carcinomas.